Natural History and Endoscopic Management of Pancreaticopleural Fistula: A Tertiary Care Center Experience - Das, Pritam; Kumar, Rakesh S.; Mujawdiya, Swapnil; Thakur, Dhruv; Wodeyar, Nagnath; Balankhe, Kartik; Saraswat, Vivek Anand; Pande, Gaurav; Mohindra, Samir (Journal of Digestive Endoscopy, 2024)
Background Pancreaticopleural fistula (PPF) is a rare complication associated with pancreatitis, caused by disruption of the pancreatic duct, either directly or through rupture of a peripancreatic fluid collection, resulting in leakage of pancreatic juice into the pleural space. It commonly presents as massive, relapsing pleural effusions, often on the left side with high amylase content. Nonspecific chest symptoms often predominate, making it a diagnostic challenge. There is a lack of clarity regarding the management of this rare entity.Objectives This study aimed to review the typical presentations, pathophysiology, and current role of endoscopic therapy in patients with PPF.Materials and Methods A retrospective analysis of the results of endoscopic treatment of patients with symptomatic PPF due to pancreatitis was done.Results Ten patients with pancreatitis (6 males; mean age 33.6 ± 15.4 years: 6 chronic, 4 acute) with symptomatic PPF were analyzed. Endoscopic retrograde cholangiopancreatography was performed in all, with pancreatic sphincterotomy and stenting of the main pancreatic duct (passive transpapillary drainage). Technical and clinical success was achieved in 7/10(70%) and 10/10(100%) patients, respectively. Though the leak was bridged in three patients, pancreatic sphincterotomy and downstream stenting (when bridging was not possible) were successful in closing PPF. One (10%) patient needed surgery for gastric outlet obstruction. The mean duration of endotherapy was 12.1 ± 9.4 months and the time taken for leak closure was 15.3 ± 10.4 weeks. Long-term success of endoscopic treatment (median follow-up period of 48.9 ± 28.7 months) was achieved in all patients.Conclusions Endoscopic treatment (passive trans-papillary drainage) is a safe and effective procedure for managing postinflammatory PPFs, and should be attempted in cases of failure of medical treatment.
Keywords: pancreaticopleural fistula; pancreatitis; pleural effusion; endoscopic retrograde cholangiopancreatography